A Novel UPLC Method for the Estimation of Antidiabetic Drugs in Bulk and its Tablet dosage form (Asian Journal of Pharmaceutics (AJP), 2024)
A highly sensitive, precise, and accurate ultra-performance liquid chromatography method was developed andvalidated for the determination of ertugliflozin and sitagliptin in the combined formulation. Chromatographicseparation was carried out on the DIKMA Endeversil C18 column (2.1 mm × 50 mm, 1.7 μm) using the mobilephase of KH2PO4:methanol 45:55 v/v. The common wavelength of absorption of ertugliflozin and sitagliptin wasfound to be 225 nm. The flow rate was maintained at 0.3 mL/min, with 2 µL injection volume. The retentiontime of ertugliflozin and sitagliptin was found to be 0.41 min and 0.535 min. % relative standard deviation of theertugliflozin and sitagliptin was found to be 0.681 and 0.218, respectively. %recovery was obtained as 100.146%and 100.27% for ertugliflozin and sitagliptin, respectively. Limit of detection (LOD), limit of quantification(LOQ) values obtained from regression equations of ertugliflozin and sitagliptin were 2.91, 2.96, and 10.04,10.09, respectively. Regression equation of ertugliflozin is y = 1329.8 × −228.7 (0.9997) and y = 1294.4.× –40.1of sitagliptin (0.9998). The proposed method was validated in terms of linearity, precision, accuracy, specificity,LOD, LOQ, and robustness. The method was successfully applied to the estimation of ertugliflozin and sitagliptintablet dosage forms.